Rumen microbial ecology: helping to change landscapes - Vercoe P.E.; Durmic Z.; Revell D.K. (Nutritional and foraging ecology of sheep and goats, 2009)
Current land use in many parts of the world is unsustainable and we face critical issues of declining soil and water quality and loss of biodiversity. In addition, more consumers now demand agricultural systems that are clean, green and ethical, where high quality and safe products are produced efficiently with minimal impact on the environment. In ruminant livestock systems, many of the consumer concerns relate to issues associated with the rumen microbial ecosystem. For example: (i) animal emissions, including the greenhouse gas, methane, from rumen fermentation and nutrient waste in faeces; and (ii) the use of antibiotics, feed additives, and anthelmintics to alter gut health and function and hormones to improve animal performance. These concerns have left producers with the challenge of remaining profitable while, at the same time, meeting market demands for product specifications from healthy animals, without relying on chemicals or harming the environment; often in locations where feed availability is limited and variable. Consequently, there is an urgent need to identify new sources of feed, including those containing natural bioactives, as safer alternatives to in-feed chemicals, to reduce methane transmissions and address animal health, production and welfare issues. With such a complex challenge, it is unlikely that any one alternative feed source will satisfy all of these necessary outcomes. A more likely scenario is that producers will need to provide animals with a greater variety of plants in polycultures. In ruminants, the success of this approach relies on the response of the ruminal microorganisms to the plants, the natural ability of the animal to select and self medicate and the management practices required by the producer to make it sustainable. In this paper we focus on in vitro screening for natural bioactives that manipulate ruminal microorganisms and how this information can be used to customise plant mixes appropriate to different land types and change landscapes.
12. Seminar on: Nutritional and Foraging Ecology of Sheep and Goats, 2007/10/11-13, Thessaloniki (Greece)